Politik Islam: Analisis Pemikiran Ibn BÄjjah Dalam KitÄb TadbÄ©r Al-Mutawahhid - Kohar, Abdul (UIN Mataram, 2020)
Ibn BÄjjah was the first Muslim philosopher in Spanish. His full name is AbÅ« Bakr Muhammad ibn yahya al-ShÄ'igh al-TujÄ©bÄ© al-SaraqustÈ‹. Ibn BÄjjah is also known by the laitin name Avempace, he is a rationalist philosopher. Many of his ideas about political, especially in the book of TadbÄ©r al-Mutawaá¸¥á¸¥id. Ibn BÄjjah said that a government have to be mutawaá¸¥á¸¥id, and mutawaá¸¥á¸¥id should be able to control themselves and be able to control lust, not to be dragged into the mainstream of society. The purpose of this research first the writer wants to say that the government (leader) is a transformation for his society, then democratic systems isnâ€™t just saying